An Analysis of Young Children's Engagement with Single and Group Interview Methods. Issue 1 (March 2016) - Ey, Lesley-anne
SEEKING CHILDREN'S PERSPECTIVES regarding matters that concern them is widely accepted and practised among researchers. Despite this, literature on research methods with young children is inconsistent. This paper reports on an analysis of semi-structured, single and group interviews conducted with six-year-old children over two visits to six diverse schools in an Australian state capital city. The findings highlighted that six-year-old children understood their role in the research process and sustained active engagement for lengthy amounts of time. This article highlights the need for researchers to critically evaluate their perspectives of children's capacity to participate in research. If researchers position children as disproportionately vulnerable, their voice could be restricted. Providing children every opportunity to express their perspectives in interviews is paramount, therefore the author presents considerations for best practice.